Awareness, knowledge, perceptions, and attitudes towards genetic testing for cancer risk among ethnic minority groups: a systematic review - Hann, Katie E. J.; Freeman, Madeleine; Fraser, Lindsay; Waller, Jo; Sanderson, Saskia C.; Rahman, Belinda; Side, Lucy; Gessler, Sue; Lanceley, Anne (BMC public health, 2017)
Background Genetic testing for risk of hereditary cancer can help patients to make important decisions about prevention or early detection. US and UK studies show that people from ethnic minority groups are less likely to receive genetic testing. It is important to understand various groups’ awareness of genetic testing and its acceptability to avoid further disparities in health care. This review aims to identify and detail awareness, knowledge, perceptions, and attitudes towards genetic counselling/testing for cancer risk prediction in ethnic minority groups. Methods A search was carried out in PsycInfo, CINAHL, Embase and MEDLINE. Search terms referred to ethnicity, genetic testing/counselling, cancer, awareness, knowledge, attitudes, and perceptions. Quantitative and qualitative studies, written in English, and published between 2000 and 2015, were included. Results Forty-one studies were selected for review: 39 from the US, and two from Australia. Results revealed low awareness and knowledge of genetic counselling/testing for cancer susceptibility amongst ethnic minority groups including African Americans, Asian Americans, and Hispanics. Attitudes towards genetic testing were generally positive; perceived benefits included positive implications for personal health and being able to inform family. However, negative attitudes were also evident, particularly the anticipated emotional impact of test results, and concerns about confidentiality, stigma, and discrimination. Chinese Australian groups were less studied, but of interest was a finding from qualitative research indicating that different views of who close family members are could impact on reported family history of cancer, which could in turn impact a risk assessment. Conclusion Interventions are needed to increase awareness and knowledge of genetic testing for cancer risk and to reduce the perceived stigma and taboo surrounding the topic of cancer in ethnic minority groups. More detailed research is needed in countries other than the US and across a broader spectrum of ethnic minority groups to develop effective culturally sensitive approaches for cancer prevention.